Aspects of Housing Development analysis of the impacts of social & economic issues on housing physical indicators (Case Study: The 2nd District of Tehran) - M. S. , Shokouhi; Toofan , Jafari (2008)
Housing development and the planning of it includes variant aspects, which are important to study, in order to have a successful plan in a city. Physical aspect contains scrutiny of seeming and objective factors of housing and dwellings, which includes kinds of building materials, quality of structure, urban accesses, and etc. Social aspect contains issues such as structure of population and household, cultural issues and etc. And economic aspect of housing include issues like cost of dwellings and real states, households’ incomes and etc. In addition, these aspects have influences on each other too. For example making changes in social and economic conditions will cause the change of physic of housing. Therefore, this paper studies impacts of social and economic situation on physic of housing in the 2nd District of Tehran as a bipolar area (in north and south of Hemmat expressway) which suffers a serious inequality in distribution of services and facilities, households’ income, cost of properties, cultural and social indicators and etc. So the relationship between physical aspect of housing and social and economic factors will be defined as a function by the two fallowing method: Factor-Analysis and Regression. This paper concludes that enhance of quality of housing is not achievable whit physical intervention merely and a comprehensive approach is necessary for housing planning.